2017
DOI: 10.4054/demres.2017.36.56
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of youth and young adults during the transition to adulthood in Egypt

Abstract: BACKGROUND There has been growing interest in the stalled transition to adulthood in the Middle East and North Africa (MENA) and its consequences for young people’s socioeconomic outcomes. However, little is known about how important life transitions relate to youth psychosocial well-being in the region. OBJECTIVE Drawing on a life course framework, we estimate the associations between making transitions in education, employment, and marriage with changes in mental health among young people in Egypt. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…Sejalan dengan penelitian Taylor et al (2011); Nurdin, Arsin dan Thaha (2018) juga menyatakan bahwa insomnia banyak dialami oleh individu pada masa produktif (18-30 tahun) karena pada kelompok usia ini kemampuan individu untuk pemecahan masalah semakin kompleks dan cukup beresiko terhadap peningkatan stress. Penurunan kualitas hidup dan insomnia pada usia produktif juga dapat dikaitkan dengan perasaan cemas, rasa sedih, tekanan, dan emosi negatif lainnya yang disebabkan oleh peristiwa di masa lalu, beratnya beban hidup, dan pola perilaku coping yang kurang tepat (Liu, Modrek & Sieverding, 2017).…”
Section: Pendahuluanunclassified
“…Sejalan dengan penelitian Taylor et al (2011); Nurdin, Arsin dan Thaha (2018) juga menyatakan bahwa insomnia banyak dialami oleh individu pada masa produktif (18-30 tahun) karena pada kelompok usia ini kemampuan individu untuk pemecahan masalah semakin kompleks dan cukup beresiko terhadap peningkatan stress. Penurunan kualitas hidup dan insomnia pada usia produktif juga dapat dikaitkan dengan perasaan cemas, rasa sedih, tekanan, dan emosi negatif lainnya yang disebabkan oleh peristiwa di masa lalu, beratnya beban hidup, dan pola perilaku coping yang kurang tepat (Liu, Modrek & Sieverding, 2017).…”
Section: Pendahuluanunclassified
“…There have been rapid demographic changes and epidemiological transitions in the region, with improvements in health status resulting in increased longevity and decreased childhood deaths. The EMR experiences a considerable burden of chronic diseases, including mental disorders (Charara et al 2017;Al-Hamzawi et al 2015;Liu 2017), and this is predicted to further increase due to ongoing unrest in the region (Charara et al 2017). Most countries in the region are prone to struggles, wars, and terrorism.…”
Section: Mental Health In the Middle Eastmentioning
confidence: 99%
“…Studies from Egypt reported that young women had worse mental health status compared to men in the same age group (Liu 2017), and that women were nearly twice more vulnerable to mental disorders compared to men, with an odds ratio of 1.8 (El-Wasify et al 2011).…”
Section: Studies Revealed Gender Differences In Mental Illness In the Emrmentioning
confidence: 99%
See 1 more Smart Citation
“…An exhaustive search of the literature on young adults transitioning to adulthood from informal kinship-based foster care found a few studies that focus on kinship-based foster care. Most studies focus on youth transitioning from formal foster care and residential care and assume that the nuclear family is the best environment (Cameroon, Hauari, & Arisi, 2018; Dziro & Rufurwokuda, 2013; Frimpong-Manso, 2012; Liu, Modrek, & Sieverding, 2017; Van Breda, 2018). This study is unique as it focuses on informal kinship-based foster care where there is no involvement of the state and where grants are not offered.…”
mentioning
confidence: 99%